New windows on the mechanism of action of K(ATP) channel openers. - Ashcroft, F; Gribble, F (2000)
K(ATP) channel openers are a diverse group of drugs with a wide range of potential therapeutic uses. Their molecular targets, the K(ATP) channels, exhibit tissue-specific responses because they possess different types of regulatory sulfonylurea receptor subunits. It is well recognized that complex interactions occur between K(ATP) channel openers and nucleotides, but the cloning of the K(ATP) channel has introduced a new dimension to the study of these events and has furthered our understanding of the molecular basis of the action of K(ATP) channel openers.